Let's copy the given equation:
![x^2+y^2+6x+8y-75=0](https://img.qammunity.org/2023/formulas/mathematics/college/ypu9tj8mt92zfaniozsgaddpa62oo09cfw.png)
To right in the center-radius form, we will have to complete the square for "x" and for "y".
The square binomial is as follows:
![(x+a)^2=x^2+2ax+a^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/eea9ekuwxh56h7u1b1fy8euvjkof1ed9ma.png)
Let's group the "x" terms and the "y" terms:
![(x^2+6x)+(y^2+8y)-75=0](https://img.qammunity.org/2023/formulas/mathematics/college/b9upcz5vjntn3etbm6xp4gbmguoqtdvro4.png)
We can see, for "x", that the quadratic term is already as we need and we have, for the first degree term:
![\begin{gathered} 6=2a \\ a=(6)/(2) \\ a=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dpd0rvijrwv67r23slhi9zbnctrk32rt3n.png)
So, if a = 3, we know that the 0th degree term is:
![\begin{gathered} a^2=(3)^2 \\ a^2=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sox5b6csr9b1za9a7md064gpgtzq9hjnex.png)
So, to complete the square, we will add 9 and, to don't change the final value, substract 9:
![\begin{gathered} (x^2+6x+9-9)+(y^2+8y)-75=0 \\ (x^2+6x+9)-9+(y^2+8y)-75=0 \\ (x+3)^2+(y^2+8y)-84=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dk5xzgxbdayycemyybnhrvi4wqvt1bs69g.png)
Now, we do the same for "y". Let's use "b" this time to don't get confused with "a". The quadratic term is correct and from the 1st degree term we get:
![\begin{gathered} 8=2b \\ b=(8)/(2) \\ b=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ng66x65mhyu465gc4axtxaprka4wkyueal.png)
So, we know that the 0th term is:
![\begin{gathered} b^2=4^2 \\ b^2=16 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b7oc8wduu729lvg7s65a7cd2z95dsd4d2x.png)
So, we add and substract 16 to comlpete the square:
![\begin{gathered} (x+3)^2+(y^2+8y+16-16)-84=0 \\ (x+3)^2+(y^2+8y+16)-16-84=0 \\ (x+3)^2+(y+4)^2-100=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jizsgv41erdpd22lwxtvizfotxzkpztwa7.png)
Now, we put the third term, which has the radius information, to the other side of the equation and take the square root and the square:
![\begin{gathered} (x+3)^2+(y+4)^2=100 \\ (x+3)^2+(y+4)^2=(\sqrt[]{100})^2 \\ (x+3)^2+(y+4)^2=10^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kvs1th9p132xhveyvhbnl9ujjmgv6lzwwg.png)
Comparing with the center-radius form:
![(x-h)^2+(y-k)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/5s77z5lwu6jnvb5vkwanu2jvhq5sh1qkc3.png)
We get:
![\begin{gathered} h=-3 \\ k=-4 \\ r=10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x2x2env74dc451zync74n8r0sut73sdaeu.png)
Since the center is C = (h, k), the answer is:
Center: (-3, -4)
Radius: 10